الظاهر والمؤول بين الفكر الأصولي والفكر التداولي المعاصر : دراسة تطبيقية مقارنة - مدحاني، يوسف أحمد عبدالله
This research aims to study the concept of Ẓahir and interpretation in Islamic heritage and contemporary pragmatic thought, theoretically and practically, through the pragmatic approach, using the descriptive analytical approach in the theoretical study of the two concepts, and the balanced comparative approach in the applied study of legal texts. It concluded that building the concept of Ẓahir must be based on Islamic heritage because it is an Islamic concept. This research also concluded that the theoretical conception of Ẓahir by most Muslim legal theorists (Al-Uṣulyyon) is “The word that indicates the meaning of the original or customary situation, and the other may be a likely possibility”. As for the pragmatic phenomenon, it appears in its inherent characteristics within the pragmatic theories, and the terms that express it in the writings of Arab pragmatic researchers, such as 'Ẓahir al nas' and the literal and original meaning. It also concluded that the theoretical conception of interpretation in Islamic heritage is “carrying the word to a language other than its Ẓahir meaning with its possibility of it, with evidence that supports it, indicating the intention of the speaker”. While pragmatic interpretation is “a process of carrying by the recipient of the text of the direct surface meaning and the literal meaning on the intended meaning of the speaker with a current contextual significance through the various concepts of pragmatics and its different mechanisms. This research also concluded that the most prominent intellectual differences in the theoretical perception of Ẓahir through pragmatic concepts: deixis, conversational implicature and speech acts, is represented in the lack of clarity of this term in the minds of Arab pragmatics. While some of them use it to mean the concept of the apparent as mentioned by scholars of the origins. It also found some of them carrying the intolerable ideas of Western pragmatics by using it to express about the literal meaning, and some of its phrases can be both. As for the intellectual discrepancies in the theoretical perception of interpretation, they are represented in the systematic difference between Arab heritage thought and pragmatic thought in its use. Despite the presence of the conceptual overlap of the term between the two thoughts, pragmatic interpretation includes what Al-Uṣulyyon have, and exceeds it. Despite this difference in them, the intellectual differences in the general theoretical concept are not great.